Assessment of landuse/landcover dynamics of Kaduna watershed, using remote sensing data and GIS techniques - Daramola, J.; Lam, K.C.; Mohd Ekhwan Toriman,; J. Mokhtar,; Salihu, Y.M.; Babayahaya, A.M.; Alakeji, J.A. (Penerbit Universiti Kebangsaan Malaysia, 2022)
Watershed assessment and developmental strategy demands precise measurement of the past and present land use parameters. Failure of Shiroro dam in 1999 and 2004 was attributes to upstream soil erosion. Hence, the study of land use change within the corridors of the reservoir for proper understanding of the watershed dynamics becomes very crucial. These dynamics was studied for a period of 38 years (1975-2013) in the Kaduna watershed, north central Nigeria using Soil and Water Assessment Tool. The land-use land cover of the year 1975, 2000, and 2013 was reclassified into nine (9) classes in 1975 and eight (8) classes in 2000 and 2013, because of the extinction of Forest evergreen land use between 1975 and 2000. The classification shows the percentage land area of each of the land use type and the area in hectares. Findings revealed total extinction of the 0.03% of Forest evergreen land before 2000, in 2013 range grasses, forestmixed and wetlands-forested land-use have lost 23.92%, 2.06%, 3.77%, watershed land area respectively while, wetlands-mixed, agricultural land, water, barren and built-up land gained 0.18%, 27.81%, 0.53%, 0.02% and 1.25% respectively as at 2013. The lost in land-use area was attributed to human activities such as clearing and degradation of the natural landscape to another land-use type which posed a stern threat to the Shiroro dam downstream and the environment. If this persists it might contribute to global warming problems and land exposure to agents of erosion. Thus, appropriate best management practice of the watershed become essential.